A TRANSLATION ANALYSIS ON THE INDONESIAN VERSION OF “DEAR GOD” BY AVENGED SEVENFOLD - Nanda Yunisa (Universitas Putera Batam, 2020)
The object of this research is the lyrics of the song Avenged Sevenfold Dear God Indonesian Version. This research discussed the translation method of the Indonesian version of the song of Dear God and aimed at finding out the translator's ideology in the translation of the Indonesian version of the song of Dear God in terms of the theory of domestication and foreignization. This study used qualitative approach with qualitative descriptive methods. The theories used in this study were theories from Newmark and Venuti, and also other theories to support this research. In this study, translators were found using the translation method which is oriented to the source text. In addition, the domestication technique looked dominant in the translation of the songs because according to Newmark (1988) this technique was the most free technique to do because it focused on the effectiveness of the target language by updating what has been provided in the source text. Thus, the translation of the Indonesian version of the song Dear God emphasizes the ideology of domestication. The result of this study indicated that translators tend to use translation methods that are oriented to the language of the target text. Additionally, it was found that the domestication technique appeared dominantly in the translation of the Indonesian version of Dear God song